2008
DOI: 10.1021/ja807942m
|View full text |Cite
|
Sign up to set email alerts
|

Reagent-Controlled Regiodivergent Resolution of Unsymmetrical Oxabicyclic Alkenes Using a Cationic Rhodium Catalyst

Abstract: A Rh(I) catalyzed regiodivergent addition of heteroatom nucleophiles to racemic oxabicyclic alkenes produces good yields of regioisomeric products each in high ee. Powerful reagent control is demonstrated, as the inherent reactivity of the substrate is completely dominated by the chiral catalyst complex, which is shown to require the use of cationic Rh(I). The process affords rapid access to multiple 1,2-dihydronapthalene products in high enantioselectivity from simple starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(49 citation statements)
references
References 22 publications
0
48
0
1
Order By: Relevance
“…What is less common is the possibility to get regioisomeric products deriving from different enantiomers of the starting material (regiodivergent kinetic resolution). [27][28][29][30][31][32] As expected, the chemical transformations performed on the enantiopure allylic substrates show a very strong catalyst control on the regioselectivity. It will be exemplified in Scheme 8, Scheme 9 and Scheme 10.…”
Section: Allylic Substitutionmentioning
confidence: 87%
See 1 more Smart Citation
“…What is less common is the possibility to get regioisomeric products deriving from different enantiomers of the starting material (regiodivergent kinetic resolution). [27][28][29][30][31][32] As expected, the chemical transformations performed on the enantiopure allylic substrates show a very strong catalyst control on the regioselectivity. It will be exemplified in Scheme 8, Scheme 9 and Scheme 10.…”
Section: Allylic Substitutionmentioning
confidence: 87%
“…The authors found that (R)-30 and (S)-30 gave different regioselectivities for a chiral ligand of a given configuration (see data in Scheme 11). For example (S)-i-PrPhox provided predominantly products Allylic substitution on some oxabicyclic systems 33 has been widely studied, especially by Lautens et al [32] Chiral rhodium complexes in methanol provided a regioselective cleavage according to the configuration of the diphosphine ligand 36 in the complex (Scheme 12). The isomeric alcohols formerly derived from the cleavage (a or b types) of the bridged oxygen, with endo attack of methanol on one or the other side of the double bond.…”
Section: Allylic Substitutionmentioning
confidence: 99%
“…Despite the dominant role exerted by bridgehead substituted oxabicyclic alkene substrates in determining ring-opening regioselectivity, it was demonstrated that a chiral Rh I catalyst can override this bias (Scheme 10.24) [23] the absolute configuration of the chiral ligand when ring-opening enantioenriched oxabicyclic alkene 60 resulted in two different regiomeric products 61 and 62.…”
Section: Mechanistic Modelmentioning
confidence: 99%
“…In the past decades, the group of Lautens and others reported rhodium-catalyzed asymmetric ring-opening of oxabenzonorbornadiene with a wide range of nucleophiles including thiols [10], phenols [11], organoboronic acids [1213], dialkylzincs [1415], carboxylates [16], sulfur nucleophiles [17], and various amines [1819]. …”
Section: Introductionmentioning
confidence: 99%